Validation Parameters as Applied to Methods for Quantification of Microorganisms in Medicinal Products - I. A. Buylova; O. V Gunar (Регуляторные исследования и экспертиза лекарственных средств, 2020)
Validation/verification of microbiological methods is a prerequisite for quality control of non-sterile drugs. However, the use of existing procedures for validation/verification of analytical methods is challenging, since a number of factors, such as microorganism distribution in the sample, cell morphology, and metabolic activity of microorganisms contribute to the error in microbiological testing.The aim of the study was to assess the feasibility of using the microbiological method validation parameters for validation/verification of the agar plate method.Materials and methods: 18 non-sterile medicinal products were used in the study. Experiments included determination of antimicrobial activity. The quantification of viable bacteria, yeasts and moulds was performed using the modified pour plate method. The statistical processing of the obtained results was performed using Microsoft Excel 7.0 and Statistica 8.0.Results: the paper provides the results of quantitative determination of test microorganisms inoculated into non-sterile drugs. The results were obtained as part of validation/verification of the agar plate method of the State Pharmacopoeia of the Russian Federation, XIV ed.Conclusions: the validation/verification of the test method for isolation and quantification of microorganisms revealed no deviations of the study results from the established acceptance criteria. This proves the feasibility of using the following validation parameters: accuracy, precision, robustness, and limit of quantitation when validating new methods for quantitative determination of microorganisms or verification of previously validated methods.